2011
DOI: 10.1002/alr.20029
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal quality‐of‐life before and after endoscopic, endonasal, minimally invasive pituitary surgery

Abstract: These data show that MIPS with appropriate postoperative care results in little or no long-term sinonasal quality of life defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…Suberman et al recently published retrospective data on sinonasal QOL in 50 patients who underwent endoscopic minimally invasive pituitary surgery. 42 These authors found no difference in Rhinosinusitis Disability Index scores from preoperative to postoperative time points, and scores were similarly unaffected by the presence or absence of a functional pituitary adenoma. Postoperative assessments were recorded at a single time point for each patient, ranging from 1 month to more than 3 years postoperatively, which may have limited the reliability of the results.…”
Section: Discussionmentioning
confidence: 91%
“…Suberman et al recently published retrospective data on sinonasal QOL in 50 patients who underwent endoscopic minimally invasive pituitary surgery. 42 These authors found no difference in Rhinosinusitis Disability Index scores from preoperative to postoperative time points, and scores were similarly unaffected by the presence or absence of a functional pituitary adenoma. Postoperative assessments were recorded at a single time point for each patient, ranging from 1 month to more than 3 years postoperatively, which may have limited the reliability of the results.…”
Section: Discussionmentioning
confidence: 91%
“…2,3,6,13,16,19 These results are providing practitioners with valuable information for managing patient expectations and modifying surgical technique to optimize QOL. A summary of recent findings is reported in Table 4.…”
Section: Discussionmentioning
confidence: 99%
“…2,8,24,25,27,31 Factors associated with increased nasal symptoms after surgery include the use of an extended endonasal approach, septal-mucosal graft, and residual tumor after surgery. 3 The strengths of these studies include the use of validated outcome measures and longitudinal follow-up that allows factors that influence QOL to be meaningfully analyzed.…”
Section: Discussionmentioning
confidence: 99%